Anak, Inses dan Problematikanya - Fitriani, Nurlinda; Najemi, Andi; Siregar, Elizabeth (PAMPAS: Journal of Criminal Law, 2024)
The purpose of writing this research is to find out and analyze how the handling of child victims of incestuous sexual violence is carried out in the Regional Technical Implementation Unit for the Protection of Women and Children in Jambi Province. The formulation of the problems in this study are: 1) how is the implementation of handling child victims of incestuous sexual violence at UPTD PPA Jambi Province, 2) what are the obstacles in carrying out handling of child victims of incest sexual violence at UPTD PPA Jambi Province. In this study the authors used empirical juridical research methods or field research based on primary data and secondary data. The results of the study show that handling child victims of incestuous sexual violence is very important to do because after the occurrence of incestuous sexual violence experienced by the victim, the victim will experience trauma because the perpetrator of the violence is the person closest to the victim. This underlies the importance of the role of UPTD PPA Jambi Province to provide treatment for child victims of incestuous sexual violence to help restore the physical and psychological condition of the child victim so as not to hinder the child's growth and development. However, in carrying out its duties and functions the UPTD PPA is constrained by several things such as: the lack of facilities and infrastructure, the lack of human resources in the field of psychology, the lack of budgetary funds in carrying out the treatment of child victims of sexual violence.